(untitled) (Philologia, 2021)
China as inspiration plays an important role in the literary work of Paul Claudel and Victor Segalen. The two French authors may be regarded as a missing link between Modernism and the literary traditions that preceded it. In this context, Claudel’s and Segalen’s interest in Chinese literary forms, language and script represents an anticipation of the later modernist preoccupations and experiments based on Chinese influences. Taking Chinese script as a role-model, Claudel attempts to iconize the symbolic system in his own language, thus creating new and authentic poetic forms, whereas Segalen introduces a very personal perception of China enriched with informative sinological observations. With their creative perception of China, both Claudel and Segalen succeeded in exerting a double influence: on one hand, they acquainted the Western reader with various valuable segments of Chinese cultural traditions, and on the other, they also provoked a series of questions concerning the role, freedom and strategies of a writer as an objective interpreter of other cultures.